Chronic diseases and obesity risk: Analysis of Turkish data - Mustafa Ikizek (National Scientific Medical Center, 2021)
Objective: Obesity is a disease with multifactorial and complex etiology. While some chronic diseases are a risk factor for the development of obesity, obesity is associated with the incidence of many chronic diseases. This study aims to determine how much chronic diseases and various socio-demographic variables increase the risk of obesity [body mass index (BMI)]. Methods:  In the study, the group of adults aged 18 and older was analyzed using a data set representing Turkey. The variables used in the analysis were obtained from the "TurkStat Health Survey" micro data set for 2016. In total, fifteen chronic disease types were analyzed using three models, seven binary regression analysis. The analyzes were carried out with 11,374 people. Results: According to the results obtained in the basic model, bronchial asthma increases the risk of obesity by 1,22 times (p<0,01), chronic bronchitis 1,31 times (p<0,001), essential hypertension 1,55 times (p<0,001), lumbar disc herniation 1,15 times (p<0,001), diabetes mellitus 1,614 times (p<0,001), and urinary incontinence 1,29 times (p<0,001), compared to people without disease (p<0,05).  According to the results obtained in the disease model, bronchial asthma increases the risk of obesity by 1,29 times (p<0,001), chronic bronchitis 1,29 times (p<0,001), essential hypertension 1,661 times (p<0,001), lumbar disc herniation 1,219 times (p<0,001), diabetes mellitus 1,625 times (p<0,001), and urinary incontinence 1,334 times (p<0,001) compared to people without disease, stroke (0,234 times), cervical disc herniation (0,671 times) and liver failure (0,502 times) reduce the risk of obesity compared to people without disease (p <0,05).  In regression models based on both disease and health models, more chronic diseases increase the risk of obesity in women compared to men. Conclusions:  Diseases such as asthma, chronic bronchitis, diabetes, urinary incontinence, hypertension, and lumbar disc herniation were found to increase the risk of obesity. Diseases that increase the risk of obesity should be fought at the source.